2020
DOI: 10.1186/s12263-020-00674-0
|View full text |Cite
|
Sign up to set email alerts
|

Low-grade chronic inflammation is attenuated by exercise training in obese adults through down-regulation of ASC gene in peripheral blood: a pilot study

Abstract: Background: Obesity is characterized by low-grade chronic inflammation and an excess of adipose tissue. The ASC gene encodes a protein that is part of the NLRP3 inflammasome, a cytosolic multiprotein complex that is associated with inflammation and metabolic alterations. To our knowledge, there is no evidence regarding ASC gene activity in obese adults in response to lifestyle modifications. Purpose: To evaluate the effect of hypocaloric diet and moderate-intensity structured exercise intervention on ASC gene … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…A decrease in the consumption of more harmful foods is related to lower CRP levels and higher levels of nutritional knowledge. This reinforces the idea of the importance of physical exercise and healthy eating for the control of inflammation [55]. Moderate physical activity was also related to an increase in nutritional knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…A decrease in the consumption of more harmful foods is related to lower CRP levels and higher levels of nutritional knowledge. This reinforces the idea of the importance of physical exercise and healthy eating for the control of inflammation [55]. Moderate physical activity was also related to an increase in nutritional knowledge.…”
Section: Discussionsupporting
confidence: 84%
“…Considering that TLR is involved in NLRP3 inflammasome activation [ 37 ], it can be postulated that exercise may also be involved in suppressing these pathways. Consistent with this notion, individualized exercise prescription has been reported to attenuate ASC gene expression in peripheral blood cells in obese individuals [ 38 ]. Animal studies have also shown that exercise suppresses NLRP3 inflammasome signaling in the aorta of obese mice [ 39 ], diabetic cardiomyopathy [ 40 , 41 ], and various brain regions, including the hippocampus [ 42 ], thus exerting protective effects against disease progression.…”
Section: Discussionmentioning
confidence: 84%
“…54 Another study by Barron-Cabrera et al also supported that changes in pro-inflammatory levels were seen in the exercise group compared to diet-only intervention, regardless of weight loss experienced by both groups. 55 Lastly, personal factors are also at play in changes in adiposity-related inflammatory markers. The review found that women had a greater reduction in pro-inflammatory levels compared to men.…”
Section: Discussionmentioning
confidence: 99%